Toxicity analysis of amoxicillin, polyphosphate ester and its complex with amoxicillin on mice - Mariia Kozak; Iryna Petruh; Iryna Kovalchuk; Vasyl Vlizlo (Scientific Reports)
Abstract Amoxicillin is one of the most widely used antibacterial drugs. It is known to be the first reason of adverse effects caused by medications in human and animals. Antibacterial drugs, combined with a delivery agent, could provide desirable therapeutic effects with decreased toxicity and reduce the emergence of antimicrobial resistant bacteria. The aim of this study was to compare the toxicity of amoxicillin, polyphosphate ester amoxicillin complex and phosphate ester on mice. Synthesis of the polyphosphate ester (P4) was performed via polycondensation technique, using PEG-400. Animal studies were performed in accordance with the European Convention for the Protection of Vertebrate Animals (Strasbourg, 1986). BALB/c mice were treated by intramuscular injection with saline 0.2 mL (control), amoxicillin 0.2 mL (15 mg/kg); polyphosphate ester complex with amoxicillin 0.2 mL (with amoxicillin content 15 mg/kg) and polyphosphate ester 0.2 mL. Blood biochemical analysis and histology of liver, spleen and kidney were used to assess toxicity. Blood biochemical analysis indicates that P4 did not induce changes in liver and kidneys. Specifically, blood biochemical indicis that represent functional state and cell structure of these organs were within normal physiological values: ALT (56 ± 15.96 U/L), AST (265 ± 37.50U/L), urea (4.4 ± 1.45 mmol/L), creatinine 62.8 ± 5.17 mmol/L, cholesterol 3.5 ± 0.56 mmol/L, total protein 55.9 ± 4.60 g/L, glucose 8.1 ± 0.55 mmol/L. However, the analysis of organ to body weight ratio showed decreased liver ratio (p ≤ 0.05) in mice injected with polyphosphate ester (P4). Histological examination of the liver didn’t show severe pathological changes. There were single places with mild portal vein inflammation in liver of mice receiving amoxicillin and amoxicillin complexed with polyphosphate ester. P4 separately in some places caused cell cytoplasm granulation in liver. No spleen alterations were observed. Overall, the results of this study showed that P4 polyphosphate ester alone and in complex with amoxicillin does not cause renal, hepatic and splenic toxicity in mice. Thus, polyphosphate ester P4 can serve as a safe drug carrier for antimicrobial drugs. It is planned to carry out more extensive studies on other animal species to study its biocompatibility and effectiveness of antimicrobial activity in a complex with antimicrobials.